MANAJEMEN PROGRAM LAYANAN BIMBINGAN DAN KONSELING BERBASIS KEARIFAN LOKAL DALAM IMPLEMENTASI 7K ANAK INDONESIA HEBAT DI SMAN 1 AIR NANINGAN - Mira Yunita; Sofwan Adiputra; Siswoyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe and analyze the management of local wisdom-based Guidance and Counseling (BK) services in the implementation of the 7K Great Indonesian Children movement at SMAN 1 Air Naningan. The background of this study is the low level of student discipline, awareness of maintaining school cleanliness, and student involvement in school activities. This condition requires systematic, contextual, and character-oriented guidance and counseling services, in accordance with local cultural values ​​and educational policies. This study used a qualitative approach with a descriptive approach. Data were collected through observation, interviews, and documentation, involving the principal, guidance and counseling teacher, teachers, and students. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The research focused on the planning, implementation, and evaluation of local wisdom-based guidance and counseling services to support the instillation of the 7K values. The results indicate that local wisdom based guidance and counseling services support the implementation of the 7K Great Indonesian Children through targeted planning, contextual service implementation, and ongoing evaluation. This program contributes to improving student discipline, awareness of cleanliness, and involvement in school activities.